Get active for mental health: a project evaluated for active involvement of families and users - Emilio Rojo Rodés; Maria Jesús San Pío Tendero; Francisco Eiroa Orosa; Gemma Marcet (International Journal of Integrated Care, 2019)
Three studies made on services users and families’ situation in Catalonia (2009-2010) reflected a need to improve the Mental Health care system in relation to: the right to information, the recovery and life project approach, participation in care, and families interventions. Therefore, in 2015, the Catalan Government (Departments of Health and Social Affairs), the Catalan Federation for Mental Health (SMC) and Federation Veus of people with self-experience, initiated the pilot project "Get active for mental health” (Activa't per la salut mental), in order to study an extension of public services portfolio. It is one of the objectives of the Integrated Plan for Mental Health and Addictions of the Catalan Government. The underlying theory is that offering easy access to information, tools for daily life, opportunities for strengthening social links and dialog between stakeholders, will enhance people with mental health problems and families to become active agents in their own process of recovery and improvement of wellbeing. This integrated approach would help to ensure equal access to support and empowerment in any point of Catalonia. The practice developed consists on introducing in current mental health and social care systems, as a complement to usual protocols and programs, a combination of four activities: information points, psychoeducation programs (Klau de Re and PROENFA), empowerment training (PROSPECT) and peer support groups. Each of the twelve pilots is driven together with a partnership of the local mental health services and users and families associations. Committees composed by professionals, users of mental health services and family members have coordinated and validated all the initiatives undertaken, online and offline materials, and some research. The evaluation method includes: a randomised controlled trial with 224 family units to measure impact, external evaluation of the implementation with qualitative and quantitative methods (both lead by Ivalua- Catalan Agency for Evaluation of public policies), external evaluation of the information services, satisfaction questionnaires, and a self- managed tool for improving the functioning of mutual-help groups. The target are both people with mental health problems, their families and professionals. From 2015 to July 2018, more than 4.000 people have participated in the pilot phase. The twelve pilot territories have replicated between three and four times this circuit. External evaluation has finished, and impact results will be available at the end of 2018. The project is designed to be transferable to all Catalonia, and financed with public funds. The final congress of the project to be held in November 2018, in Barcelona, will allow presentation of the results, making balance of the pilot phase and discuss improvements needed and details of its extension to all Catalonia, through participation and debate with all the stakeholders. Pending from final evaluation reports and conclusions of the final congress, some preliminary key findings and lessons learned can be pointed out: the project has been very welcomed by most stakeholders, all activities have had high satisfaction rates from participants, the circuit needs to become shorter and more flexible, further updating of the project and extension to other groups are demanded.